2021
DOI: 10.15562/jdmfs.v6i2.1232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pup out® on caspase 3 and interleukin-1B expression in pulp teeth: a paste contained jatropha, sidaguri, and melittin

Abstract: Objective: To examine the expression of caspase-3 and IL-1β following application of Pulp Out® on rabbit's pulp teeth as well as histopathology. Material and Methods:The study was conducted on the maxillary incisors rabbits. The teeth were prepared and Pulp Out® was inserted at the base of prepared cavity, then restored with RM-GIC. After 24 hours, the animals were then euthanized and processed for histopathology and immunohistochemistry evaluation. Results:Our results indicated that Pulp Out®, when administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…7 Combination of jatropha sap, root of sidaguri and mellitin, namely Pulp-Out has been reported to cause pulpal cell death following its application into tooth cavity that showed similar cell death of commercial devitalizing agents. 8 In previous in vitro study, a decreased of tooth hardness and erosion were reported which was in line with duration and dosage of Pulp-Out applied. 9 It is assumed that the extracts are able to penetrate through the porosity formed and causing cell death.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…7 Combination of jatropha sap, root of sidaguri and mellitin, namely Pulp-Out has been reported to cause pulpal cell death following its application into tooth cavity that showed similar cell death of commercial devitalizing agents. 8 In previous in vitro study, a decreased of tooth hardness and erosion were reported which was in line with duration and dosage of Pulp-Out applied. 9 It is assumed that the extracts are able to penetrate through the porosity formed and causing cell death.…”
Section: Introductionmentioning
confidence: 62%
“…The image of cell death is similar to commercial devitalizing agent, arsen trioxide. 8 However the mechanism of pulpal cell death is not really understood. The finding of previous in vitro study on prepared human teeth showed erosion and a decrease of dentin tooth hardness following pulp out application.…”
Section: Original Researchmentioning
confidence: 99%
“…Some herbs have also been studied to have the potency to be developed as a pulp devitalizing agent to devitalize dental nerves in root canal treatment. Our previous study observed that these combined herbal extracts, namely Pulp Out, caused pulpal cell death in animal study following its application in exposed pulp which showed similar image of cell death of commercial pulp devitalizing agent, marked by the presence of changes and lysis in the cell nucleus [5] .…”
Section: Introductionmentioning
confidence: 76%
“…The Pulp Out paste was prepared according to the previous methods described by Tanumihardja et al [5] . The root of sidaguri and sap of jatropha were collected from Bone, South Sulawesi, Indonesia, in May 2021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation